Call for Papers: Demography Prize for Young Researches 2016/2017 - IF and FRFG (Intergenerational Justice Review)
The Stuttgart-based Foundation for the Rights of Future Generations (FRFG) and the London-based Intergenerational Foundation (IF) jointly award the biennial Demography Prize, endowed with EUR 10,000 (ten thousand euros) in total prize-money, to essay-writers who address political and demographic issues pertaining to the field of intergenerational justice. The prize was initiated and is funded by the Stiftung Apfelbaum.